The Bologna Process, beyond the structural changes: a vision from Medical Education in Spain - Jorge Palés Argullós (Universitat Politècnica de València, 2012)
The Bologna process, which started in 1998, aims to harmonize European Higher Education facilitating the mobility of students and professors and determines the adoption of a system of comprehensive and comparable degrees, facilitated by the implementation of the so-called Diploma Supplement; the adoption of a system based on three cycles, Bachelor, Master and PhD, and the implementation of a common system of credits known as ECTS (European Credit Transfer System). But further of the inherent structural appearances to the Bologna process, to which considerable interest has been shown, and to which a lot of time and discussion has been devoted, there are other important educational aspects that underlie Bologna process, and that have not generally received the attention that would have been desirable. The Bologna process involves, from the educational point of view, a paradigm shift, from a teacher-centered education process, to a student-centered learning process; from the process- based education to outcome and competencies-based education, leading to the need for an adequate assessment of these competencies. In this article we will refer mainly to these aspects, which in my opinion are the key elements of this process.